The Effectiveness of Visual Media in Improving Students’ Arabic Language Learning According to Edgar Dale's Cone of Experience Model - Novianty, Nur'ain; Rochmat, Cecep Sobar; Shodik, Adam Ja'far (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study examines the effectiveness of visual media in improving students’ Arabic language learning based on Edgar Dale's Cone of Experience framework. A descriptive qualitative design with a literature review method was employed. Data were collected from scholarly sources related to visual media, Arabic language learning, and Dale's experiential model. The data were analyzed using thematic analysis, consisting of initial coding, code categorization, and theme development. The results indicate that visual media significantly contribute to simplifying abstract concepts, strengthening memory retention, and increasing students’ motivation in learning Arabic. Its effectiveness becomes more evident when connected to Dale’s Cone of Experience, which highlights visual symbols as an essential stage for bridging abstract ideas with concrete experiences. Overall, this study underscores that visual media not only support students’ comprehension but also enhance the achievement of Arabic language learning objectives.